Improving the Management of Diansati Waste Bank Through Digitalization of Marketing and Financial Management - Mauliddah, Nurullaili; Hafiizh Tantri, Ashr; Melynda Sari, Tyasha Ayu; Monalisa, Monalisa; Artikawati Santoso, Oktavia (IMPOWERMENT SOCIETY, 2025)
Surabaya is inseparable from environmental health problems. The threat of disease due to the lack of environmental sanitation is a problem that always arises in everyday life. The concept of zero waste as a lifestyle aims to minimize the amount of waste produced every day, one of which is through reduce, recycle and reuse. Proper waste management will provide its own value to the community from both economic and social aspects. This community service activity uses an active participation approach with the Diansati Waste Bank social community. Bank Sampah Diansati has been using a manual packing activity process by stepping on foot. The activity process goes through the stages of program socialization, preparation of press machine design, preparation of social media design and e-commerce, demonstration of the use of tools, utilization of tools by partners, monitoring and evaluation. Partners in this community service activity have 32 members. The results of community service activities show that partners can utilize tools and get convenience with the hydraulic waste press machine. In addition, recycled products by partners such as shampoo from water hyacinth can be sold online, which so far has been sold in the neighborhood around the partner.